Bone and Joint Infection Involving Corynebacterium spp.: From Clinical Features to Pathophysiological Pathways - Chauvelot, Pierre; Ferry, Tristan; Tafani, Virginie; Diot, Alan; Tasse, Jason; Conrad, Anne; Chidiac, Christian; Braun, Evelyne; Lustig, Sébastien; Laurent, Frédéric; Valour, Florent (Frontiers in Medicine, 2021)
Introduction: Corynebacteria represent often-neglected etiological agents of post-traumatic and/or post-operative bone and joint infection (BJI). We describe here clinical characteristics and bacteriological determinants of this condition. Methods: A retrospective cohort study described characteristics, outcome and determinants of treatment failure of all patients with proven Corynebacterium spp. BJI (i.e., ≥2 culture-positive gold-standard samples). Available strains were further characterized regarding their antibiotic susceptibilies, abilities to form early (BioFilm Ring Test®) and mature (crystal violet staining method) biofilms and to invade osteoblasts (gentamicin protection assay). Results: The 51 included BJI were mostly chronic (88.2%), orthopedic device-related (74.5%) and polymicrobial (78.4%). After a follow-up of 60.7 weeks (IQR, 30.1-115.1), 20 (39.2%) treatment failures were observed, including 4 Corynebacterium-documented relapses, mostly associated with non-optimal surgical management (OR 7.291; p=0.039). Internalization rate within MG63 human osteoblasts was higher for strains isolated from delayed (>3 months) BJI (p<0.001). Infection of murine osteoblasts deleted for the 1-integrin resulted in a drastic reduction in the internalization rate. No difference was observed regarding biofilm formation. Conclusions: Surgical management plays a crucial role in outcome of BJI involving corynebacteria, as often chronic and device-associated infections. Sanctuarisation within osteoblasts, implicating the 1 cellular integrin, may represent a pivotal virulence factor associated with BJI chronicity.